Effects of Pre-ovulatory Follicular Fluid of Repeat Breeder Dairy Cows on Bovine Fertility Transcriptomic Markers and Oocytes Maturation and Fertilization Capacity - Kafi, Mojtaba; Ghaemi, Mehran; Azari, Mehdi; Mirzaei, Abdolah; Azarkaman, Samad; Torfi, Yusof (Frontiers in Veterinary Science, 2021)
The current study aimed to determine the effects of the preovulatory follicular fluid (FF) of normal heifer (NH) and repeat breeder cows with subclinical endometritis (SCE) or without (nSCE) on oocyte maturation (Experiment 1) and fertilization rates (Experiment 2). Moreover, the pattern of gene expression of cumulus oocyte-complexes was evaluated in Experiment 1. In Experiment 1, nuclear maturation in the nSCE group was higher, compared to that in the SCE group (P=0.05). In addition, the oocyte nuclear maturation in the normal heifer was significantly higher, in comparison to that of SCE groups (P<0.05). Furthermore, the mean percentage of normal oocyte fertilization was higher in the nSCE group, compared to that in the SCE group (P<0.05). The expressions of all genes (GDF9, StAR, and FSHr) in the NH group were significantly higher, compared to those in SCE and nSCE groups (P<0.05). Moreover, the expressions of all genes in the nSCE group were not significant, in comparison to those in the SCE group (P>0.05). The supplementation of oocyte maturation medium with FF from pre-ovulatory follicles of repeat breeder cows resulted in less oocyte maturation and cumulus cell expansion. In conclusion, the lower fertility in RB cows could be ascribed to the lower oocyte developmental competence and less expression of GDF9, StAR, and FSHr in the cumulus-oocyte complexes.